2013
DOI: 10.1007/s12639-013-0299-0
|View full text |Cite
|
Sign up to set email alerts
|

Studying the correlations among hematological and serum biochemical constituents in cattle theileriosis

Abstract: The present study was undertaken to investigate the influence of tropical theileriosis on serum constituents, erythrocytes and platelets pictures and to study the correlation between the studied parameters. A total number of 26 cows were subjected to study. Out of them 16 cows were suffered from theileria infection. Comparing theileria infected group with the control group revealed significant decreases in total RBCS counts (p \ 0.01), haemoglobin concentration (p \ 0.01), packed cell volume (PCV) (p \ 0.01), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Leukopenia in the terminal stage could have resulted from large-scale destruction of lymphocytes by schizogony in lymphoid organs and infiltration of these cells into various organs (Sandhu et al 1998). The thrombocytopenia with decreased RBCs and WBCs could also be related to increased TNF-α production (Forsyth et al 1999) or suppression of the bone marrow by the parasite and its products (Abd Ellah 2015; Mbassa et al 1994). In this study, the levels of IL-6, TNF-α and IFN-γ were increased from the onset to the middle course of disease and decreased in the terminal stage of disease in infected sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Leukopenia in the terminal stage could have resulted from large-scale destruction of lymphocytes by schizogony in lymphoid organs and infiltration of these cells into various organs (Sandhu et al 1998). The thrombocytopenia with decreased RBCs and WBCs could also be related to increased TNF-α production (Forsyth et al 1999) or suppression of the bone marrow by the parasite and its products (Abd Ellah 2015; Mbassa et al 1994). In this study, the levels of IL-6, TNF-α and IFN-γ were increased from the onset to the middle course of disease and decreased in the terminal stage of disease in infected sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, MPV (fL) values in whole blood (3.11 ± 0.06) from the cows used in this study were lower than the same parameter reported in healthy cows in which whole blood (6.30 ± 0.17) was obtained with EDTA [39]. However, PDW (%) values in whole blood (16.47 ± 0.10) from our cows were higher than the same value reported for whole blood (10.70 ± 0.30) of healthy cows using EDTA [39]. …”
Section: Discussionmentioning
confidence: 63%
“…However, the values for these parameters could change as a function of the anticoagulant used for blood collection and the technology of the device used for measurement [15, 38, 40, 41]. Notably, MPV (fL) values in whole blood (3.11 ± 0.06) from the cows used in this study were lower than the same parameter reported in healthy cows in which whole blood (6.30 ± 0.17) was obtained with EDTA [39]. However, PDW (%) values in whole blood (16.47 ± 0.10) from our cows were higher than the same value reported for whole blood (10.70 ± 0.30) of healthy cows using EDTA [39].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Anaplasma marginale and Anaplasma centrale of the order Rickettsiales are the main causes of anaplasmosis, which was once referred to as gall sickness [Di Domenico et al 2016;Sivajothi and Reddy, 2022]. Sheep, goats, and other ruminants in the wild are susceptible to Anaplasma ovis [Abd Ellah, 2015;Hornok et al 2011]. Some forms of Babesia have been found in the family Cervidae [France, 2004].…”
Section: Introductionmentioning
confidence: 99%